To determine the convergence or divergence of the series `sum_(n=1)^oo (-1)^n/(n!)` , we may apply the Ratio Test.

In **Ratio test**, we determine the limit as:

`lim_(n-gtoo)|a_(n+1)/a_n| = L`

Then ,we follow the conditions:

a) `L lt1` then the series converges absolutely

b) `Lgt1` then the series diverges

c) `L=1 ` or does not exist then the test is inconclusive.The series may be divergent, conditionally convergent, or absolutely convergent.

For the given series `sum_(n=1)^oo (-1)^n/(n!)` , we have `a_n =(-1)^n/(n!)` .

Then, `a_(n+1) =(-1)^(n+1)/((n+1)!)` .

We set up the limit as:

`lim_(n-gtoo) | [(-1)^(n+1)/((n+1)!)]/[(-1)^n/(n!)]|`

To simplify the function, we flip the bottom and proceed to multiplication:

`| [(-1)^(n+1)/((n+1)!)]/[(-1)^n/(n!)]| =| (-1)^(n+1)/((n+1)!)*(n!)/(-1)^n|`

Apply Law of Exponent: `x^(n+m) = x^n*x^m` . It becomes:

`| ((-1)^n (-1)^1)/((n+1)!)*(n!)/(-1)^n|`

Cancel out common factors `(-1)^n` and apply `(-1)^1 = -1`

`| -(n!)/((n+1)!) |`

Simplify:

`| -(n!)/((n+1)!) |=(n!)/((n+1)!)`

` =(n!)/(n!(n+1))`

` =1/(n+1)`

The limit becomes:

`lim_(n-gtoo)1/(n+1) =(lim_(n-gtoo) (1))/(lim_(n-gtoo) (n+1) )`

`= 1/(oo+1)`

` =1/oo`

` =0`

The limit value` L=0` satisfies the condition: `L lt1` .

Therefore, the series `sum_(n=1)^oo (-1)^n/(n!) ` is **absolutely convergent**.